New directions and paradigms for the study of Greek architecture : interdisciplinary dialogues in the field - Sapirstein, Philip; Scahill, David (Monumenta Graeca et Romana, 2020)
"New Directions and Paradigms for the Study of Greek Architecture comprises 20 chapters by nearly three dozen scholars who describe recent discoveries, new theoretical frameworks, and applications of cutting-edge techniques in their architectural research. The contributions are united by several broad themes that represent the current directions of study in the field, i.e.: the organization and techniques used by ancient Greek builders and designers; the use and life history of Greek monuments over time; the communication of ancient monuments with their intended audiences together with their reception by later viewers; the mining of large sets of architectural data for socio-economic inference; and the recreation and simulation of audio-visual experiences of ancient monuments and sites by means of digital technologies. Contributors are: Lena Lambrinou; Vasileia Manidaki; Jeanne Capelle; Alexander Tanner; Nancy L. Klein; Nils Hellner; D. Matthew Buell, John C. McEnroe, Jorge Andreas Botero Besadalombana, Rafał Bieńkowski; Yannos Kourayos, Kornilia Daifa, Goulielmos Orestidis, Dimitrios Egglezos, Vasilis Papavasileiou, Eleni-Eva Toumpakari; Kyle A. Jazwa; András Patay-Horváth; Mark Wilson Jones; Silke Müth; Sarah A. Rous; Matthias Grawehr; Mary B. Hollinshead; Miriam G. Clinton, Ansel MacLaughlin; Christian Fron, Verena Stappmanns, Xiaoru Zhou, Philip Leistner; Clemente Marconi, David Scahill, Massimo Limoncelli; Bonna D. Wescoat"--